2018
DOI: 10.1111/mec.14829
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation underlying local adaptation of diapause induction along a cline in a butterfly

Abstract: Diapause is a life history strategy allowing individuals to arrest development until favourable conditions return, and it is commonly induced by shortened day length that is latitude specific for local populations. Although understanding the evolutionary dynamics of a threshold trait like diapause induction provides insights into the adaptive process and adaptive potential of populations, the genetic mechanism of variation in photoperiodic induction of diapause is not well understood. Here, we investigate gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 78 publications
5
83
0
Order By: Relevance
“…Outliers were identified as non-overlapping windows of 50 kb within the 0.5% of lowest and highest genetic differentiation per comparison. To reduce the number of false-positive results, the outlier threshold was chosen at 0.5% highest and lowest percentile of each pairwise genetic differentiation 74, 75 . To find candidate genes within windows of highest differentiation, a total of three selection criteria were used.…”
Section: Methodsmentioning
confidence: 99%
“…Outliers were identified as non-overlapping windows of 50 kb within the 0.5% of lowest and highest genetic differentiation per comparison. To reduce the number of false-positive results, the outlier threshold was chosen at 0.5% highest and lowest percentile of each pairwise genetic differentiation 74, 75 . To find candidate genes within windows of highest differentiation, a total of three selection criteria were used.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies in two other insects show that per alleles are associated with polymorphism in the timing of 253 autumnal initiation of diapause (critical photoperiod for entrance) (68,69). Genetic changes at per may 254 therefore provide the capacity to adjust diapause transition times across two different seasons, enabling 255 insects to synchronize with both the end and beginning of winter.…”
mentioning
confidence: 99%
“…For instance, the circadian clock gene timeless was found to be in control of diapause incidence (Sandrelli et al, ) and allele frequencies of timeless alleles differentially affecting diapause induction behaviour were shown to covary over latitude (Tauber et al, ) in Drosophila . This pattern, a functional role of one or several circadian clock genes in the control of diapause induction and associated cline in allele frequencies for these genes in natural populations is recurrently observed, e.g., for the parasitic wasp Nasonia vitripennis ( period, cycle and cryptochrome ; Paolucci, Salis, Vermeulen, Beukeboom, & Zande, ) or more recently for the speckled wood butterfly ( period & timeless ; Pruisscher, Nylin, Gotthard, & Wheat, ). However, Emerson, Dake, Bradshaw, and Holzapfel () found that the photoperiodic seasonal clock in control of diapause can evolve independently from the circadian clock.…”
Section: Introductionmentioning
confidence: 95%